2018
DOI: 10.5468/ogs.2018.61.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroids and outcomes of preterm small-for-gestational-age neonates in a single medical center

Abstract: ObjectiveThis study investigated the effect of an antenatal corticosteroid (ACS) in preterm small-for-gestational-age (SGA) neonate.MethodsThis study was a retrospective cohort study. We compared women who received ACS with unexposed controls and evaluated neonatal complications among those having a singleton SGA neonate born between 29 and 34 complete gestational weeks. The neonates born after 32 weeks of gestation were divided into subgroups. Multivariable logistic regression analysis was performed.ResultsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Preclinical and clinical evidence demonstrates that antenatal steroids may exacerbate growth restriction (particularly repeat doses) (18) and that the FGR fetus differentially responds to antenatal steroids compared to appropriately-grown fetuses, likely mediated via altered placental response to steroids (19). Antenatal glucocorticoids may not significantly improve neonatal outcomes in FGR preterm infants (20), and indeed, may have adverse effects on brain development (21, 22). Further research is clearly needed in this area.…”
Section: Etiology and Uteroplacental Factorsmentioning
confidence: 99%
“…Preclinical and clinical evidence demonstrates that antenatal steroids may exacerbate growth restriction (particularly repeat doses) (18) and that the FGR fetus differentially responds to antenatal steroids compared to appropriately-grown fetuses, likely mediated via altered placental response to steroids (19). Antenatal glucocorticoids may not significantly improve neonatal outcomes in FGR preterm infants (20), and indeed, may have adverse effects on brain development (21, 22). Further research is clearly needed in this area.…”
Section: Etiology and Uteroplacental Factorsmentioning
confidence: 99%
“…Rather, ACS seemed to increase the risk of RDS. They concluded that ACS therapy for women who are at risk for preterm delivery with IUGR fetus, need to be further evaluated, espe cially after 32 weeks of gestation [13]. A recent meta-analysis, examined 16 observational cohort and case-control studies published from 1995 to 2018, they concluded that ACS reduces neonatal mortality in SGA infants delivered preterm, with no apparent effect on neonatal morbidity (RDS, NEC, IVH and periventricular leukomalacia, bronchopulmonary dysplasia or chronic lung disease of prematurity, or neonatal sepsis).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported no effect of ACS on neonatal morbidity or mortality among IUGR fetuses in the early preterm (up to 34 weeks of gestational age) [8,11,12,13,14]. Van Stralen et al demonstrated that administration of ACS to IUGR fetuses does not appear to be bene cial with respect to short term neonatal outcome in preterm deliveries [8].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm prelabor rupture of membranes (PPROM) is defined as rupture of membranes before 37 weeks [2]. Both SGA and PPROM infants are at an increased risk for adverse outcomes [2][3][4], and SGA appears to complicate pregnancies with preterm labor and PPROM more often than uncomplicated pregnancies [5,6]. Therefore, the accurate prediction of SGA in pregnancies with PPROM will assist in creating surveillance protocols to reduce such adverse outcomes [7].…”
Section: Introductionmentioning
confidence: 99%